The demand for crop genetic resources: international use of the US National Plant Germplasm System - Smale, Melinda; Hodgkin, T.; Zohrabian, Armineh; Day-Rubenstein, Kelly (International Food Policy Research Institute, 2001)
In contrast to a perception that ex situ collections of germplasm are rarely used, this empirical case study reveals large quantities of germplasm samples distributed by the U.S. National Germplasm System to many types of scientific institutions located in numerous countries around the world. Distributions favor developing countries in several ways including the numbers of samples shipped, utilization rates in crop breeding programs, and the secondary benefits brought about through sharing this germplasm with other scientists. Expected future demand is also greater among scientists in developing countries. These findings underscore the importance to global science and technology of retaining such resources in the public domain.